ENHANCING STUDENTS’ LEARNING OUTCOMES IN SCIENCE AND SOCIAL SUBJECTS THROUGH WORDWALL TOURNAMENT GAMES - Nasution, Fadhlun Nisa; Aprilianti, Ersya Suci; Aisyah, Nyimas; Asnaningsih, Julia (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2025)
The science learning outcomes of 4th-grade students at SDN 09 Palembang have been consistently low, largely due to ineffective teaching methods. This research addresses this issue by improving science learning outcomes by implementing a game-based learning approach using Wordwall Tournament games. This research employs a classroom action research (CAR) design conducted over two cycles, each consisting of planning, implementation, observation, and reflection. The research was conducted with 18 students from 4th grade (class A) at SDN 09 Palembang during the odd semester of the 2024/2025 academic year. Data were collected through observations and tests. The success standard for this research was set at a minimum of 75% of the student population, fulfilling the minimum passing grade (KKM) of 75. The findings indicate that using tournament-style educational games effectively enhances student learning outcomes. This improvement is shown by increased student achievement across the research cycles. Only 8 out of 18 students fulfilled the learning objectives during the pre-cycle stages, with a completion rate of 44% and an average score of 54.71. In Cycle I, 12 out of 18 students achieved the learning objectives, with a completion rate of 67% and an average score of 64.72. This progress continued in Cycle II, where 16 out of 18 students met the objectives, with a completion rate of 89% with an improved average score of 78.11. These results indicate that implementing Wordwall Tournament games has significantly improved science learning outcomes among 4th-grade students